Prime Minister’s Decree No. 2220 of the Year 2025 - Prime Minister (The Middle East Library For Economic Services, 2025)
on reducing the selling prices of electricity supplied to industrial activities on the ultra-high, high and medium voltage by ten piasters per kilowatt hour outside and inside peak times